Odpowiedź :
Odpowiedź:
1) [tex]3\frac{1}{6} - 1\frac{1}{2} = 1\frac{2}{3}[/tex]
2) [tex]\frac{1}{6} + \frac{1}{2} : 3 \\\\[/tex]
[tex]\frac{2}{3} : \frac{3}{1}[/tex]
[tex]\frac{2}{3} * \frac{1}{3}[/tex] = [tex]\frac{2}{9}[/tex]
Szczegółowe wyjaśnienie:
Pozdrawiam, miłej nocy
Odpowiedź:
[tex]\frac{3\frac{1}{6}-1\frac{1}{2}}{\frac{1}{6}+\frac{1}{2}:3}=[/tex]
[tex](3\frac{1}{6}-1\frac{3}{6}):(\frac{1}{6}+\frac{1}{2}*\frac{1}{3})=[/tex]
[tex](2\frac{7}{6}-1\frac{3}{6}):(\frac{1}{6}+\frac{1}{6})=[/tex]
[tex]1\frac{4}{6}:\frac{2}{6}=\frac{10}{6}*\frac{6}{2}=5[/tex]
Szczegółowe wyjaśnienie: